Differential effects of fingolimod on B-cell populations in multiple sclerosis. (September 2014) - Nakamura, Masakazu; Matsuoka, Takako; Chihara, Norio; Miyake, Sachiko; Sato, Wakiro; Araki, Manabu; Okamoto, Tomoko; Lin, Youwei; Ogawa, Masafumi; Murata, Miho; Aranami, Toshimasa; Yamamura, Takashi
Background: Fingolimod is an oral drug approved for multiple sclerosis (MS) with an ability to trap central memory T cells in secondary lymphoid tissues; however, its variable effectiveness in individual patients indicates the need to evaluate its effects on other lymphoid cells. Objective: To clarify the effects of fingolimod on B-cell populations in patients with MS. Methods: We analysed blood samples from 9 fingolimod-treated and 19 control patients with MS by flow cytometry, to determine the frequencies and activation states of naive B cells, memory B cells, and plasmablasts. Results: The frequencies of each B-cell population in peripheral blood mononuclear cells (PBMC) were greatly reduced 2 weeks after starting fingolimod treatment. Detailed analysis revealed a significant reduction in activated memory B cells (CD38 int-high ), particularly those expressing Ki-67, a marker of cell proliferation. Also, we noted an increased proportion of activated plasmablasts (CD138 + ) among whole plasmablasts, in the patients treated with fingolimod. Conclusions: The marked reduction of Ki-67 + memory B cells may be directly linked with the effectiveness of fingolimod in treating MS. In contrast, the relative resistance of CD138 + plasmablasts to fingolimod may be of relevance for understanding the differential effectiveness of fingolimod in individual patients.